Comparative Analysis of Housing Systems: Microclimate, Production Performance, and Economic Efficiency in Broiler Housing System - Fadilah, Roni; Elly Tugiyanti; Rosidi; Ismoyowati; Novie Andri Setianto (ANIMAL PRODUCTION, 2025)
Microclimate conditions significantly influence broiler production efficiency in tropical climates. This study evaluated microclimate conditions and their impact on production and economic efficiency in open, semi-closed, and closed housing systems. The research was conducted on three commercial farms representing each housing system in West Java. Microclimate parameters (temperature, relative humidity, heat stress index) and production performance (body weight, FCR, mortality, production index) were measured over one production cycle. Results showed that the closed-house system maintained significantly better microclimate conditions with lower temperature deviations (brooding: -0.52°C; post-brooding: -0.35°C) compared to open (1.06°C; 5.11°C) and semi-closed houses (0.07°C; 1.54°C). The closed-house system achieved significantly higher final body weight (2397.6 g/bird), production index (434), and income over feed cost (Rp 31,238/bird) compared to other systems. Correlation analysis revealed strong negative relationships between temperature parameters and production performance (p<0.01). The closed-house system demonstrated superior microclimate control, leading to significantly improved production efficiency and economic returns.